Lactobacillus acidophilus-Induced Endocarditis and Associated Splenic Abscess - Muhammet Ozer; Suleyman Yasin Goksu; Ali Shahverdiani; Muhammad Mustafa (Case Reports in Infectious Diseases)
Lactobacillus acidophilus is a rod-shaped, Gram-positive bacterium generally found in the normal flora of the oropharynx, gastrointestinal, and genitourinary tracts. It is commonly known as nonpathogen in the human body. Endocarditis due to Lactobacillus is rarely encountered and associated with impaired immunity. Splenic abscess is also an uncommon infection that classically results from endocarditis or another source of hematogenous seeding. Here, we present the case of bioprosthetic aortic valve endocarditis and associated splenic abscess caused by Lactobacillus acidophilus. The source of the Lactobacillus bacteremia should be investigated because of the risk of life-threatening conditions. Most of the time, identifying Lactobacillus species is challenging and can cause a delay in diagnosis and timely treatment. Especially in patients who have significant underlying clinical conditions, physicians should consider Lactobacillus species as a causative microorganism.